Tilletia thirumalachari- a new smut species from Maharashtra - KANCHANGANGA GANDHE, R.V. GANDHE and (Indian Phytopathology, 2002)
Tilletia thirumalachari n. sp. is described from Setaria verticillata collected in Pune, Maharashtra, India. The sori, spores and sterile cells of the new species are described and compared with those of 5 other Tilletia spp. that infest Setaria spp.